Phylogenomic relationships and species delimitation of Cotoneaster ser. Pannosi, ser. Buxifolii, and related taxa - Huang, Jiaxuan; Chen, Sufang; Meng, Kaikai; Li, Mingwan; Zhao, Wanyi; Wang, Na; Fan, Qiang; Liao, Wenbo (Frontiers in Plant Science, 2025)
Polyploidy and hybridization are prevalent phenomena within the genus Cotoneaster, leading to blurred species boundaries, particularly in Cotoneaster ser. Pannosi and Cotoneaster ser. Buxifolii. This study seeks to establish a robust phylogenetic framework for these series and their allied taxa to support future taxonomic revisions and investigations of hybridization–polyploidy dynamics. Population-level sampling was conducted across 43 populations located in Sichuan, Taiwan, Yunnan, Tibet (China), and Rasuwa (Nepal), including 17 species from C. ser. Pannosi and C. ser. Buxifolii, along with 10 species from closely related series. Following detailed comparisons with type specimens, six quantitative traits were measured, and 16 qualitative traits were recorded from individual specimens, followed by hierarchical clustering and principal component analyses of the combined dataset. Phylogenetic relationships were reconstructed using two datasets: 1) chloroplast genomes generated through shallow genome sequencing and 2) single-nucleotide polymorphisms (SNPs) obtained from restriction site-associated DNA sequencing (RAD-seq), complemented by genetic structure analyses. The taxonomic framework equally prioritizes nuclear clade monophyly [Shimodaira–Hasegawa approximate likelihood ratio test (SH-aLRT) ≥ 80% and ultrafast bootstrap (UFboot) ≥ 95%] and discrete genetic cluster membership (cluster assignment probability ≥ 95%) as primary delimitation criteria, complemented by morphological discontinuity (≥ 2 traits) and chloroplast phylogeny concordance. Fourteen species satisfied all criteria, corresponding to nine distinct gene pools, while the remaining 13 species displayed admixed genomic compositions and cytonuclear discordances, indicative of hybrid origins. This study identifies putative hybrid taxa and provides a foundational framework for further species delimitation, advancing future research on Cotoneaster systematics, natural hybridization patterns, and taxonomic revision.